До задачі про стійкість руху істотно нелінійних систем - Мартинюк, А.А.; Чернієнко, В.О. (Доповіді НАН України, 2021)
Для істотно нелінійних систем рівнянь збуреного руху запропоновано один підхід для оцінки функцій Ляпунова вздовж розв’язків розглянутих систем рівнянь. Як застосування розглянуто задачу про обмеженість і стійкість руху істотно нелінійної системи рівнянь другого порядку, задачі про стійкість при великих початкових збуреннях та про стійкість неавтономної афінної системи. This article discusses essentially nonlinear systems. Following the approach of applying the pseudolinear inequalities developed in a number of works, new estimates for the variation of Lyapunov functions along solutions of the considered systems of equations are obtained. Based on these estimates, we obtain sufficient conditions for the equiboundedness of solutions of second-order systems and sufficient conditions for the stability of an essentially nonlinear system under large initial perturbations. Conditions for the stability of affine systems are also obtained.